Inhibition of Gamma-Secretase Promotes Axon Regeneration After a Complete Spinal Cord Injury - Sobrido-Cameán, Daniel; Robledo, Diego; Romaus-Sanjurjo, Daniel; Pérez-Cedrón, Vanessa; Sánchez, Laura; Rodicio, María Celina; Barreiro-Iglesias, Antón (Frontiers in Cell and Developmental Biology, 2020)
In a recent study, we showed that GABA and baclofen (a GABAB receptor agonist) inhibit caspase activation and promote axon regeneration in descending neurons of the sea lamprey brainstem after a complete spinal cord injury (Romaus-Sanjurjo et al., 2018a). Now, we repeated these treatments and performed 2 independent Illumina RNA-Sequencing studies in the brainstems of control and GABA or baclofen treated animals. GABA treated larval sea lampreys with their controls were analyzed 29 days after a complete spinal cord injury and baclofen treated larvae with their controls 9 days after the injury. One of the most significantly downregulated genes after both treatments was a HES gene (HESB). HES proteins are transcription factors that are key mediators of the Notch signaling pathway and gamma-secretase activity is crucial for the activation of this pathway. So, based on the RNA-Seq results we subsequently treated spinal cord injured larval sea lampreys with a novel gamma-secretase inhibitor (PF-3804014). This treatment also reduced the expression of HESB in the brainstem and significantly enhanced the regeneration of individually identifiable descending neurons after a complete spinal cord injury. Our results show that gamma-secretase could be a novel target to promote axon regeneration after nervous system injuries.